The hunter [large type]: a novel - Lescroart, John T. (Wheeler Pub. Large Print, 2012)
"Raised by loving adoptive parents, San Francisco private investigator Wyatt Hunt never had an interest in finding his birth family-until he gets a chilling text message from an unknown number: "How did ur mother die? The answer is murder, and Hunt takes on a case he never knew existed, one that has lain unsolved for decades. His family's dark past unfurls in dead ends.The texter, who insists the killer is out there, refuses to be identified. The cat-and-mouse game leads Hunt across the country and eventually to places far more exotic and dangerous. As the chase escalates, so does the threat, for the killer has a secret that can only be trusted to the grave" -- Cover verso.